2015
DOI: 10.1039/c5rp00058k
|View full text |Cite
|
Sign up to set email alerts
|

Perceived autonomy-support, expectancy, value, metacognitive strategies and performance in chemistry: a structural equation model in undergraduates

Abstract: Research in chemistry education has highlighted a number of variables that predict learning and performance, such as teacher-student interactions, academic motivation and metacognition. Most of this chemistry research has examined these variables by identifying dyadic relationships through bivariate correlations. The main purpose of this study was to simultaneously investigate students' perceptions of teacher-student interactions (autonomy support), motivation (expectancy, importance, utility and interest), me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 68 publications
4
31
0
2
Order By: Relevance
“…Despite the widely discussed relationship between motivation and metacognition as primary components of SRL (see Figure 1), we found only one study of HE students which investigated this relationship. [38] This lack stands in contrast to the relationship between metacognition and cognition, which was investigated in all the studies we found, wherein learning performance stood in as an operational measure of cognition. Perhaps unsurprisingly, González and Paoloni [38] reported that motivation predicted use of metacognitive strategies, and that both motivation and metacognitive strategies predicted students' learning performance.…”
Section: Metacognition Of Higher Education Studentsmentioning
confidence: 67%
See 2 more Smart Citations
“…Despite the widely discussed relationship between motivation and metacognition as primary components of SRL (see Figure 1), we found only one study of HE students which investigated this relationship. [38] This lack stands in contrast to the relationship between metacognition and cognition, which was investigated in all the studies we found, wherein learning performance stood in as an operational measure of cognition. Perhaps unsurprisingly, González and Paoloni [38] reported that motivation predicted use of metacognitive strategies, and that both motivation and metacognitive strategies predicted students' learning performance.…”
Section: Metacognition Of Higher Education Studentsmentioning
confidence: 67%
“…González and Paoloni, 2015 [38] Perceived autonomy-support, expectancy, value, metacognitive strategies and performance in chemistry: a structural equation model in undergraduates.…”
Section: Author/s and Yearmentioning
confidence: 99%
See 1 more Smart Citation
“…the education system as a whole, their families, and the social environment enveloping them, among other personal, intrapersonal, interpersonal, contextual and situational elements (Vallerand & Blssonnette, 1992). It is linked to student learning (Chiu & Chow, 2010;González & Paoloni, 2015;Yen, Tuan, & Liao, 2011), and has been scientifically evaluated by several authors due to its influence on the learning process (Deci & Ryan, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Por tanto, el aprendiz se prepararía para detectar sus dificultades y tratar de autorregular su aprendizaje. En caso de no lograrlo, tendría que considerar la posibilidad de buscar ayuda para poder continuar (Briceño, 2009;González y Paolini, 2015;Mathabate y Potgieger, 2014;Schunk y Zimmerman, 2013).…”
unclassified